They called themselves the K.K.K. : the birth of an American terrorist group - Bartoletti, Susan Campbell (Houghton Mifflin Harcourt, 2010)
Documents the history and origin of the Ku Klux Klan from its beginning in Pulaski, Tennessee, and provides personal accounts, congressional documents, diaries, and more.